Prevalence of drug resistance in clinical isolates of tuberculosis from GCC: a literature review from January 2002 to March 2013 - Areeshi, Mohammed Yahya; Bisht, Shekhar Chandra; Mandal, Raju Kumar; Haque, Shafiul (The Journal of Infection in Developing Countries, 2014)
Introduction: The prevalence of drug resistance in clinical isolates of Mycobacterium tuberculosis from the Gulf Cooperation Council (GCC; Saudi Arabia, Qatar, Bahrain, Kuwait, Oman, United Arab Emirates [UAE]) countries was appraised using reports published between January 2002 and March 2013. Methodology: A total of 11,393 tuberculosis (TB) isolates from the GCC were studied through published literature and were analyzed statistically. Results: Most of the isolates were resistant to isoniazid, followed by streptomycin, rifampin, ethambutol, and pyrazinamide. The highest prevalence rate of multidrug-resistant-TB (MDR-TB) was found in UAE (9.2%), followed by Kuwait (5.9%) and Saudi Arabia (4.3%). The overall MDR-TB prevalence rate was recorded as 4.0% in the entire GCC region. Automated linear modeling revealed that isoniazid resistance had a strong relationship with the prevalence of MDR-TB in all the GCC countries and was found to be the strongest predictor for MDR-TB. Interestingly, rifampicin resistance was significantly associated with the prevalence of MDR-TB in Oman, Kuwait, and Saudi Arabia, while isoniazid was identified for UAE. On the basis of a number of reports and isolates, the principal component analysis showed that, among all GCC member countries, the highest burden of TB was in Saudi Arabia and Kuwait, and maximum drug resistance was present in UAE. Conclusion: The study demonstrates that the prevalence of MDR-TB in GCC countries is almost equal to other developing and developed countries, and requires immediate attention for surveillance and control.